Developing pubertal guidance application media for mild intellectual disabled students at SLB Negeri 1 Pinrang - astuti reski pratama; Usman Bafadal; Farida Aryani (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2021)
This research is aimed to find out (1) the description of media analysis. (2) the prototype of pubertal guidance application media. (3) the validity and practicality of the guidance application media for mild intellectual disabled students, made in the form of an application designed to display several lessons. This research method is a research and development (R&D), stage of research by Borg & Gall. Researchers applied interview data collection, questionnaires, and validation test instruments. The results showed that (1) an overview of the media needs for pubertal guidance applications was required for teachers and students with mild intellectual disability for puberty guidance (2) a prototype of pubertal guidance application media was developed in the form of an android application contained material contents, videos, and evaluations (3) based on a test, the validity and the practicality of the pubertal guidance application was valid and practical, applicable on the pubertal guidance class for mild intellectual disability students.